From Waste to Wealth: Conceptualizing the Recycling Process as a Pathway to Sustainable Civil Engineering Practices - Muhamad Rifandi (Advanced Business Journal, 2025)
The construction industry is one of the largest generators of waste and consumers of natural resources worldwide. This study presents a conceptual analysis of the recycling process within civil engineering sites, emphasizing its role in sustainable construction and circular economy practices. Using a qualitative and descriptive approach, the research synthesizes findings from global studies, reports, and industry data to develop a framework outlining five key stages of the recycling process—waste generation, segregation, processing, quality control, and reuse. The results show that effective recycling can reduce construction waste by up to 90%, lower material costs by 5–10%, and cut carbon emissions by approximately 20%. The study further identifies challenges such as limited policy support, lack of standardization, and technological gaps that hinder wide-scale adoption, particularly in developing countries. The proposed conceptual framework highlights that recycling is not only a technical solution but also a management and policy process requiring coordination among engineers, contractors, and regulators. Overall, the study concludes that integrating systematic recycling into project planning and execution can transform civil engineering into a resource-efficient, low-carbon industry, aligning with global sustainability objectives such as the UN Sustainable Development Goals (SDGs).